FOXE1 Mutation Screening in a Case with Cleft Lip, Hypothyroidism, and Thyroid Carcinoma: A New Syndrome? - Hugo Mendieta-Zerón; Angélica Jiménez-Rosales; Carlos Jhovani Pérez-Amado; Silvia Jiménez-Morales (Case Reports in Genetics)
A 26-year-old woman is referred to the Internal Medicine consultation due to increases in laboratory studies associated with Papillary Thyroid Carcinoma (PTC) that was confirmed by histopathological studies. Her clinical history revealed that, at 3 months of age, she was successfully treated with surgery for cleft lip (CL) and at the age of 24 years was diagnosed with hypothyroidism. Single nucleotide polymorphisms (SNPs) in FOXE1 and its promoter regions have been associated with various etiologies related to the thyroid, including orofacial clefting, specially cleft palate (CP) and CL, hypothyroidism (HT), and thyroid cancer. The association of CL, HT, and PTC might be component of a new syndrome; however FOXE1 coding region, which has been involved with these entities, has not exhibited mutations or SNPs. Further study of other genes may help in better characterization of the possible syndrome.